GeoGebra Training for Making Mathematics Learning Media at SMPN 11 Depok - Roni Al Maududi; Rini Widia Putri; Purni Munah Hartuti (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this community service activities is to introduce and provide a GeoGebra training to Mathematics teachers at SMP Negeri 11 Depok. GeoGebra is a software that is used as a learning media in Geometry and Algebra as an innovation in learning Mathematics. So far, teachers are using simple tools only to explain about some topics in Mathematics to the students. The community service team will introduce and give a GeoGebra training. The methods that are used are training methods, accommodation, and discussion. The training is carried out by providing theories and practices to the teachers to operate the GeoGebra for Geometry and Algebra. The output target in this community service is the teachers can use GeoGebra as a learning media in Mathematics especially in Geometry and Algebra, GeoGebra module, and scientific articles.